Artistic Image in the Years of Lead - De Oliveira Elias, Tatiane (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2017)
The Brazilian dictatorship (1964-1984) directly influenced Brazilian arts. Various artists addressed death, torture, and riot scenes in their works. This era of upheaval and oppression played an important role in Brazilian visual art, films, music, theater, literature and politics and is very important to understand avant-garde art of the time and the pronounced changes of the arts in general. In this paper I will examine the ways in which Brazilian artists have expressed and responded to the social, economic and political crisis of dictatorship. Moreover they resisted American cultural imperialism and displayed culture and social realities of Brazil.